Distant Drums And Thunderous Cannon: Sounding Authority In Traditional Malay Society - Andaya, Barbara Watson (Penerbit Universiti Sains Malaysia (USM Press), 2011)
Pre-modern Malay society was intensely oral and aural, and the texts that are now read were always intended for group recitation and performance. Studies of auditory history in other societies have emphasised that in the past, sounds were experienced differently from the way they are heard today. At the very basic level, thunder—the voice of the heavens—established the benchmark and the basis for comparison for awe-inspiring sounds that humans could attempt to replicate, notably in the beating of drums and the firing of cannon. Together with the noseflute, the drum is the oldest and most indigenous Malay instrument, and the drums that were included in royal regalia were accorded personalities of their own.